The Influence of School Policy and Practice on Mathematics Achievement During Transitional Periods - Janet K. Holt; Cynthia Campbell (Arizona State University, 2004)
In this study, the effects of school policies and practices on math achievement growth, as students transitioned from middle to high school, were examined while controlling for school contextual variables. A pattern of accelerated growth in mathematics achievement from grades 8 to 12 occurred, in which higher achieving students in mathematics at grade eight accelerated more than lower achieving students in mathematics growth during the transition from middle to high school. Controlling for school context, school policy promoting parent involvement and academic counseling had significant positive impacts on the acceleration in growth during this period. The implications of using multilevel growth models to study growth during transition periods are discussed.